2018
DOI: 10.1007/s00394-018-1607-3
|View full text |Cite
|
Sign up to set email alerts
|

Is vitamin D deficiency a public health concern for low middle income countries? A systematic literature review

Abstract: Vitamin D deficiency is a public health issue in some, but certainly not all, LMICs. There is a clear need for targeting public health strategies for prevention of vitamin D deficiency in those LMICs with excess burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 110 publications
1
81
0
1
Order By: Relevance
“…Although several recent review papers have highlighted the global extent of vitamin D deficiency, there are significant data gaps, especially for LMICs . Representative population‐level 25(OH)D data are not available for most countries, and the surveys that do exist often present an incomplete picture of vitamin D status and its determinants (i.e., lacking complementary data related to dietary intake, UVB exposure).…”
Section: Global Prevalence Of Vitamin D Deficiencymentioning
confidence: 99%
“…Although several recent review papers have highlighted the global extent of vitamin D deficiency, there are significant data gaps, especially for LMICs . Representative population‐level 25(OH)D data are not available for most countries, and the surveys that do exist often present an incomplete picture of vitamin D status and its determinants (i.e., lacking complementary data related to dietary intake, UVB exposure).…”
Section: Global Prevalence Of Vitamin D Deficiencymentioning
confidence: 99%
“…We wish to emphasize that inadequate vitamin D intakes and vitamin D deficiency in pregnant and lactating women are very common worldwide, thus pointing to the need to improve vitamin D status [ 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 ]. A systematic review has shown that 25(OH)D concentrations below 50 and 25 nmol/L during pregnancy were reported in 64% and 9% of Americans, and 57% and 23% of Europeans [ 127 ].…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…15 Prevalence of low serum 25(OH)D levels and inadequate exposure and intake of vitamin D has been recorded in the general population by many studies exhibiting clear regional difference in the extent of concern. 16,17 Our report involved analysis of vitamin D status for comparing the prevalence of VDD as well as VDI between two tropical countries, India and Bahrain. Though there is major difference in the socio-economic, cultural as well as diet and lifestyle factors between the two regions, abundance of sunlight which is the most important for vitamin D was the common ground.…”
Section: Discussionmentioning
confidence: 99%